As with any long division problem, you start with the most significant terms of the dividend and divisor

This is the first term of the quotient.

As with any long division problem, you multiply this by the divisor, subtract from the dividend and repeat.

(x^3 + x^2 + x - 3) - x^2(x-1)

= 2x^2 + x - 3

The second term of the quotient will be

2x^2/x = 2x

The new dividend is

(2x^2 + x - 3) - 2x(x-1)

= 3x - 3

We can see that this is 3(x-1), so the remaining term of the quotient is 3.

**.**x^3/x = x^2This is the first term of the quotient.

As with any long division problem, you multiply this by the divisor, subtract from the dividend and repeat.

(x^3 + x^2 + x - 3) - x^2(x-1)

= 2x^2 + x - 3

The second term of the quotient will be

2x^2/x = 2x

The new dividend is

(2x^2 + x - 3) - 2x(x-1)

= 3x - 3

We can see that this is 3(x-1), so the remaining term of the quotient is 3.

**The quotient is x^2 + 2x + 3**.